2019
DOI: 10.1016/j.neo.2019.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Targeting c-MYC through Interference with NAMPT and SIRT1 and Their Association to Oncogenic Drivers in Murine Serrated Intestinal Tumorigenesis

Abstract: We recently described a positive feedback loop connecting c-MYC, NAMPT, DBC1 and SIRT1 that contributes to unrestricted cancer cell proliferation. Here we determine the relevance of the loop for serrated route intestinal tumorigenesis using genetically well-defined Braf V600E and K-ras G12D mouse models. In both models we show that c-MYC and SIRT1 protein expression increased through progression from hyperplasia to invasive carcinomas and metastases. It correlated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…In some cases, NAMPT was found to be a direct transcriptional target of c-Myc, resulting in a positive feedback loop between c-Myc, NAMPT, and SIRT1 that drove tumor cell proliferation and progression (74)(75)(76). These studies showed that the use of NAMPT inhibitors resulted in a loss of SIRT1 expression, derepression of TP53, and decreased tumor cell growth in CRC models (74,75,77). A similar effect has been observed in prostate (19) and gastric cancer models (78).…”
Section: Sirtuin Functionmentioning
confidence: 58%
See 2 more Smart Citations
“…In some cases, NAMPT was found to be a direct transcriptional target of c-Myc, resulting in a positive feedback loop between c-Myc, NAMPT, and SIRT1 that drove tumor cell proliferation and progression (74)(75)(76). These studies showed that the use of NAMPT inhibitors resulted in a loss of SIRT1 expression, derepression of TP53, and decreased tumor cell growth in CRC models (74,75,77). A similar effect has been observed in prostate (19) and gastric cancer models (78).…”
Section: Sirtuin Functionmentioning
confidence: 58%
“…Among these insights are an appreciation of the role of NAMPT in sirtuin expression (73). In CRC models, several groups have reported that regulation of SIRT1 activity is mediated by NAMPT (74)(75)(76)(77). In some cases, NAMPT was found to be a direct transcriptional target of c-Myc, resulting in a positive feedback loop between c-Myc, NAMPT, and SIRT1 that drove tumor cell proliferation and progression (74)(75)(76).…”
Section: Sirtuin Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…SIRT1, in turn, stabilizes c-MYC and enhances its transcriptional activity, and promotes tumorigenesis through the attenuation of p53 activity and the inhibition of c-MYC-induced apoptosis [ 38 ]. This c-MYC–NAMPT–SIRT1 positive feedback loop was found to be activated in colorectal carcinoma and its interruption was proposed as a viable therapeutic intervention [ 59 , 60 ]. Additionally, the high-mobility group A (HMGA1) protein was reported to be another protein regulating NAMPT expression through a different enhancer element [ 39 ].…”
Section: Regulation Of Nad Production In Cancer Cellsmentioning
confidence: 99%
“…One of the key stimulators of mitochondrial biogenesis is the c-myc oncogene, which activates the expression of genes that regulate the cycles of mitochondrial fusion and fission to expand the mitochondria content in the cell [ 96 ]. In actively proliferating cells, the expression of c-myc leads to the activation of the NAD+-synthesizing enzyme (NAMPT), an increase in the level of NAD+ and an increase in the activity of sirtuin 1 (NAD+-dependent histone deacetylase); thereby, mitotic activity and cell viability are preserved [ 97 ]. However, other evidence suggests that expression of c-myc causes an increase in glycolytic activity in proliferating cells and leads to a decrease in NAD + levels [ 98 ].…”
Section: Mitochondrial Dysfunction and Nvu/bbb Impairment In Alzheimer’s Type Neurodegenerationmentioning
confidence: 99%